A Review of Vitamin D Deficiency in the Critical Care Population - Kelly Massey; Roland N. Dickerson; Rex O. Brown (MDPI AG, 2014)
It is well documented that a large percentage of the general population is either vitamin D insufficient or deficient. Vitamin D deficiency adversely affects bone health. More recently, it has been reported that vitamin D is an important component in immune function and glycemic control Substantial data exist that demonstrate an association between vitamin D insufficiency/deficiency and mortality/clinical outcomes of critically ill patients. The larger clinical trials addressing this association have demonstrated an increased odds ratio for mortality in both vitamin D insufficient and deficient patients when compared to those with sufficient vitamin D. There is also some evidence that vitamin D status worsens during critical illness without supplementation of this vitamin. Supplementation of vitamin D during critical illness of patients with vitamin D deficiency has been studied, but not in great detail. Daily supplementation of the recommended dietary allowance (RDA) of vitamin D does very little to improve the 25(OH)D serum concentrations in the critically ill patients with vitamin D insufficiency or deficiency. There is some evidence that high-dose therapy of vitamin D improves the depressed serum concentrations of this vitamin; however, there are no clinical outcome data available yet. The association between vitamin D insufficiency or deficiency and clinical outcome in the critically ill appears to be important. Supplementation of vitamin D will increase the serum concentrations of this vitamin; however the optimal dose needs to be identified along with an assessment of clinical outcome.